Exploring the State-of-the-art in Plug-in Hybrid Electric Vehicle Design and Modeling: A Review - Sarvesh Koli; Manmath Mokal; Vishal Patil; Reena Tandel; Pragati Shinde; B.R Patil (International Journal of Electrical Machine Analysis and Design, 2024)
This document provides a thorough explanation of the process involved in designing and developing plug-in hybrid electric vehicles (PHEVs). A viable way to lessen greenhouse gas emissions and reliance on conventional internal combustion engine vehicles is through plug-in hybrid electric vehicles (PHEVs), which have gained popularity in response to growing concerns about environmental sustainability and the depletion of fossil fuels. The main elements, design factors, difficulties, and developments in the field of plug-in hybrid electric vehicles are covered in this paper. Additionally, it investigates how to improve the performance and efficiency of plug-in hybrid electric vehicles (PHEVs) by integrating smart grid systems, battery technology, and renewable energy sources. The purpose of this study is to offer insights that will aid in the continuous research and development related to sustainable transportation.
Keywords: Design; Plug-in hybrid electric vehicles; Renewable energy; Smart grid; Sustainability; battery technologies; development